The Miller Revival (1831-1844): Waiting for Christ Return... - Darius, Fábio Augusto (2014)
The Baptist farmer William Miller, in solitary study — equipped with Cruden’s Concordance and his King James Bible — started a great movement of revival in the United States. According to their calculations, Christ literally returns in the sky between March 1843 and March 1844. Great was the disappointment of their fans when the expected does not happen. The article discusses the concepts of Miller on the books of Daniel and Revelation, key to understanding the historical events and transcendent of the Second Advent.